THE STUDY OF FREE RADICALS TO EVALUATE THE HEALING EFFECTS OF PUNICA GRANATUM PEEL ON ACETIC ACID-INDUCED COLITIS IN RATS - VERMA, ARPIT; GOEL, MANI; PRAJAPATI, SATYENDRA; BHADKARIYA, ANAND (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to analyze the effect of 50% ethanolic extract of the dried Punica granatum peel (PGE) on the healing of acetic acid-induced colitis in rats. Methods: Colitis was induced in rats using 50% acetic acid and then PGE extract was administered by oral route daily for 14 days to those rats. Optimal healing was observed by the administration of a 100 mg/kg dose of PGE extract. Effectiveness of the above-mentioned dosage of PGE on biochemical parameters, basically free radicals – nitric oxide and lipid peroxidation was studied on 18 hours fasting rats on the 15th day of the experiment. Results: The results were suggestive of the healing properties of PGE extract by reduction of the inflammation and mucosal damage in the colon of those rats. The healing effects were established by the estimation and study of free radicals taken from the mucosal samples of the rat’s colon. The safety of extract was established by the effective administration of 10 times the therapeutic dose, that is, 1000 mg/kg dosage of the PGE extract with no noticeable adverse effects or side effects related to ANS or central nervous system. Conclusion: PGE extract was found to be effective in healing mucosal damage due to colitis by controlling the infection and reducing the inflammation.